Chronic Disease Decision Making and "What Matters Most". Issue 3 (11th February 2020) - Fried, Terri R.; Street, Richard L.; Cohen, Andrew B.
Abstract : The increasing use of the question, "What matters most to you?" is a welcome development in the effort to provide patient‐centered care. However, it is difficult for clinicians to translate answers to this question into treatment plans for chronic conditions, including recognizing when to consider options other than clinical practice guideline (CPG)–directed therapy. Goal elicitation is most helpful when a patient has different treatment options with clearly identifiable trade‐offs. In the face of trade‐offs, goal elicitation helps patients to prioritize among potentially competing outcomes. While decision aids (DAs) focus on trade‐offs by delineating options and outcomes, the robust outcome data necessary to create DAs for older patients with multimorbidity are often lacking and even mild cognitive impairment makes the use of DAs difficult. The challenges for providing chronic disease care to older patients who are at risk for adverse events from CPG‐directed therapy because of multimorbidity and/or frailty are to organize the complexity of individual combinations of diseases, conditions, and syndromes into common sets of trade‐offs and to identify those goals or priorities that will directly inform a plan of care. J Am Geriatr Soc 68:474–477, 2020